Ethnopharmacology of five flowers herbal tea, a popular traditional beverage in Hong Kong and South China - Kwun-Tin Chan; Hoi-Yan Wu; Wing-Yee Tin; Paul Pui-Hay But; Sidney Chin-Hung Cheung; Pang-Chui Shaw (BMC, 2024)
Abstract Background It has been a long-standing tradition of using herbal tea for preventive and therapeutic healthcare in Hong Kong and South China and Five Flowers Tea is one of the most popular herbal teas. Based on the principle of traditional Chinese medicine, the pharmacological functions are to clear heat and dispel dampness in the body. Heat and dampness are thought to contribute to a range of health problems, especially during the hot and humid season in South China and Hong Kong. The most prevalent herbs in the formula contain bioactive compounds including flavonoids, alkaloids and terpenoids, which have a wide range of pharmacological properties including anti-inflammation, antivirus, antidiarrhoea, antibacteria, and antioxidation. However, with the composition varies widely, the ethnopharmacological benefits described may not be delivered uniformly. This study is to provide a comprehensive analysis on the composition of the Five Flowers Tea sold in Hong Kong and investigate the rationale behind the selection of herbs used in the formula. This study also provides information on the variation and quality of the Five Flowers Tea in the market. Methods Thirty-three Five Flowers Tea samples were collected from various locations in Hong Kong. The size, texture, colour and organoleptic properties were documented. Macroscopic and molecular authentication methods were employed to identify the individual components. Results Macroscopic identification revealed there were 23 herbs belonging to 18 plant families. The most prevalent herb was Bombax ceiba L., followed by Chrysanthemum morifolium. Ten adulterants and the existence of insect Lasioderma serricorne were confirmed by DNA barcoding techniques. Conclusion This study employed a comprehensive approach to authenticate the herbs in Five Flowers Tea samples collected from various locations in Hong Kong. Macroscopic and molecular methods were used to identify the herbs and adulterants. The findings revealed the varied composition in Five Flowers Tea and the occurrence of adulterants in some samples. This shows that quality assurance of Five Flowers Tea is essential for the effective use of this popular folk medicine.